‘Aeroimages’ and Urban Visions of Rome between the Wars (diségno, 2023)
At the beginning of the last century, the experience of flying by airplane favoured the development of a new sensitivity towards the city and the territory. It transcends the static visions of the hot-air balloon and introduces a dynamic and, in some ways, anti-perspective sense, even in the urban representation. This article focuses on the twenty years of fascism and the case of Rome, which the historical events made the main development centre for the new-born aeronautics; investigates the relationship between the work of futurist artists, who created new figurative methods in aeropittura (aeropainting), and that of architects, increasingly committed to providing bird’s-eye views of large urban projects; identifies in some architects and drawings the signs of a new way of representing the city and of interpreting architecture from above, in connection with the surrounding territory, which testify to the airplane experience both directly and mediated by photography and cinema; finally, it witnesses the resistance of conventional architectural graphic models and the architects’ general inability to grasp the suggestions offered by the artists.
Keywords: Futurism; aeropittura; bird’s-eye view; photography; urban design